Komunikasi Lintas Agama dan Misi Keagamaan: Analisis Tantangan dan Solusi - Nurazam, Ifan Faqih; Karami, Gergian Abi (Hikmah, 2024)
Interfaith communication is an important aspect in an increasingly complex multicultural society. This research aims to identify the challenges faced in interfaith communication, including stereotypes, prejudices, incomprehensibility of the teachings of other religions, cultural differences, and social pressures. In addition, this study also explores solutions that have been implemented to improve interfaith dialogue, such as inclusive interfaith education, structured dialogue, cooperation in social projects, and the use of social media. Religious missions are also analyzed as factors that can serve as bridges or barriers in interfaith communication, depending on the approach. This study proposes an effective model of interfaith communication based on the principles of equality, openness, and respect for differences, and supported by education and social cooperation. The results of this research are expected to contribute to building harmonious relationships between religious communities in a multicultural society